PELATIHAN PENYUSUNAN PROPOSAL SKRIPSI MAHASISWA SEBAGAI UPAYA MENGHASILKAN PENELITIAN YANG BERKUALITAS - Mustofa Meihan, Andre; Robbi Kurniawanti, Merci; Yosephine Sinurat, Junita; Hajri, Priazki (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Training in preparing student thesis proposals is a very strategic activity to improve students' abilities in designing relevant and quality research and of course has many positive benefits for students. The method used in this service activity is to deliver material directly and provide assistance to Jambi University History Education Study Program students in designing a quality thesis proposal. The results of this training have been said to be successful because the participants were able to prepare research proposals well and in accordance with the thesis writing guidelines at Jambi University. With an average score of 82 in the A category.